1996
DOI: 10.1021/jp953735c
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Energy Transfer

Abstract: Many aspects of the collision dynamics of vibrational energy transfer are presented. Special emphasis is placed on three broad areas within this field:  (1) vibrational energy transfer in large molecules (>10 modes) at low excitation, (2) vibrational energy transfer in large molecules at high vibrational excitation, and (3) vibrational energy transfer of highly excited small molecules. Advances in laser methods have revolutionized experimental investigations of all of these areas. Recent results are presented,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
169
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(176 citation statements)
references
References 423 publications
7
169
0
Order By: Relevance
“…This work confirmed the existence of what have been termed [20][21][22][23] multi-quantum (MQ) and sequential, single-quantum (SQ) mechanisms of energy transfer in this and related systems. The former process consists of direct population transfer between vibration states, often over many vibrational quanta, within a target molecule, CsH in this case.…”
Section: T V Of Csh(v;j) In H 2 500 Ksupporting
confidence: 78%
See 2 more Smart Citations
“…This work confirmed the existence of what have been termed [20][21][22][23] multi-quantum (MQ) and sequential, single-quantum (SQ) mechanisms of energy transfer in this and related systems. The former process consists of direct population transfer between vibration states, often over many vibrational quanta, within a target molecule, CsH in this case.…”
Section: T V Of Csh(v;j) In H 2 500 Ksupporting
confidence: 78%
“…These findings mirror those reported by Wodtke et al on vibrationally excited O 2 and NO. [20][21][22][23] (iv) The experimental cross section for the initial, MQ fall of T v was calculated to be 4.6 ± 1.1 Å 2 .…”
Section: T V Of Csh(v;j) In H 2 500 Kmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas early work focused principally on molecules in low vibrational levels, 27 the development of stimulated emission pumping 28 and of overtone pumping 29 has allowed investigation of species in highly excited vibrational states. 2 Light collision partners are much more effective quenchers of large vibrational energy gaps than heavy species for molecules in low and high vibrational states. Single quantum relaxation often dominates, even when the diatomic is highly excited and evidently there are limits to the amount of energy that may be released on collision however much is contained initially within vibrational modes.…”
Section: Relaxation Pathways In Polyatomic Moleculesmentioning
confidence: 99%
“…1 However the number of additional excitation and relaxation routes in polyatomic molecules brings new possibilities, raising fundamental questions concerning the dynamical behavior of molecules. [2][3][4][5][6] Parmenter, 2 Rice 3 among others have drawn attention to the extraordinarily selective nature of vibrational transfer ͑VT͒ in large molecules. Waclawik and Lawrance 4,5 demonstrated that angular momentum ͑AM͒ factors exercise a controlling influence on VT in excited benzene.…”
Section: Introductionmentioning
confidence: 99%